Has economic growth reduced poverty in Nigeria? A critical analysis of the last two decades - Tikristini Olasode; Chukwuemeka Eke; Olalekan Oluwabunmi Olaleye (Journal of Enterprise and Development (JED), 2022)
Purpose — This paper aims to examine how Nigeria's economic growth over the past two decades has contributed to poverty reduction.Method — This study adopted the desktop research method of qualitative and quantitative data and used various sources, including academic journals, publications, books, articles, and reports. The National Bureau of Statistics (NBS) of Nigeria, the United Nations Development Programme (UNDP), the Human Development Report, the World Bank Indicators, and the Central Bank of Nigeria (CBN) Statistical Bulletin are all places where secondary statistical data comes from.Result — Nigerian economy has experienced significant growth over the last two decades, but poverty rates in the country remain high. We also discovered that the Nigerian economy's high level of inequality, corruption, jobless growth, and monocity are some issues that have hindered the translation of economic growth into significant poverty reduction.Recommendation — Based on the analysis of this research and the peculiarity of the Nigerian economy, this paper recommends that diversification of the economy, investment in public services, and policies that encourage pro-poor growth are effective strategies that would lead to more significant poverty reduction. In addition, there is a need to study the nature of inequality in Nigeria. An in-depth study needs to be done on income inequality and the multidimensional forms of inequality prevalent in the country.Contribution — Research on economic growth and poverty in Nigeria mostly concentrated on the relationship between these variables. Only a few studies have investigated why the poverty rate continues to rise amid economic growth. This study tries to fill this gap and contribute empirically to the current literature on economic growth and poverty in Nigeria by studying the economic situations and factors surrounding the country's rising poverty rate.